(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
This study aims to analyze the internal and external factors that influence the growth of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Lasiana Village using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis approach. The research method applied is qualitative, with data collection techniques including in-depth interviews, field observations, and documentation reviews of culinary MSMEs selected purposively based on specific criteria. The data obtained is then analyzed using the SWOT framework to formulate relevant and applicable development strategies for increasing the competitiveness of MSMEs in the region. The results of the study show that the main strengths of culinary MSMEs in Lasiana Village lie in their strategic business locations, competitive product prices, and high level of operational flexibility in adjusting to market demand. However, there are still a number of weaknesses that need to be addressed, such as low product innovation, limited managerial capabilities, and suboptimal use of digital technology. On the other hand, there are considerable opportunities for development, including improving the quality of human resources through training programs, diversifying more innovative products, optimizing digital marketing, expanding online marketing networks, and strengthening sustainable product innovation. Based on the results of the SWOT analysis, there are several strategies that can be recommended to accelerate the growth of culinary MSMEs in Lasiana Village. First, increasing human resource capacity through training programs provided by the government and related institutions. Second, developing sustainable product innovation to expand market segments and increase consumer appeal. Third, optimizing the use of digital platforms as a means of promotion and marketing to expand market reach. Fourth, strengthening managerial aspects through structured mentoring and entrepreneurship training activities. With the consistent implementation of these strategies, culinary MSMEs in Lasiana Village are expected to be able to strengthen their competitiveness, grow sustainably, and make a more significant contribution to the local economy.